The Practice of Adu Rasa, Angon Rasa, and Njaga Rasa in the Speech Act of Javanese Kiai: An Ethnopragmatic Study - Setiawan Edi Wibowo (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2020)
The current research is an ethnopragmatic study which aims to describe the practice of adu rasa, angonrasa, and njaga rasa in the speech act of the Javanese kiai. This research is an ethnographic field study. The data are the speeches of kiai from Central Java (Rembang and Demak) and East Java (Tuban) in the religious preaching activities, and they are provided through explanatory text. They are collected by observation and documentation through recording, observing and note-taking. The ability to understand, to see, and to remain considerate towards the interlocutor is necessary to make sure the communication runs very well. The practice of adu rasa, angon rasa and njaga rasa in the speech act of Javanese kiai is manifested in; (1) the speech act for convincing others under the principle of adu rasa and angon rasa (reassurance and sensibility management); (2) the speech act for convincing others under the principle of showing concern; and (3) the speech act for inviting others to do something (recommendation) under the principle of adu rasa and angon rasa.Keywords: Speech Acts, Ethnopragmatics, Adu Rasa, Angon Rasa, Javanese Kiai